2008
DOI: 10.1007/bf03395599
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Reversal Learning in Capuchin Monkeys (Cebus Apella)

Abstract: Learning styles in capuchin monkeys were assessed with a computerized reversal-learning task called the mediational paradigm. First, monkeys were trained to respond with 90% accuracy on a two-choice discrimination (A+B-). Then the authors examined differences in performance on three different types of reversal trials (A-B+, A-C+, B+C-), each of which offered differing predictions forperformance, depending on whether the monkeys were using associative cues or rule-based strategies. Performance indicated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 28 publications
1
31
0
1
Order By: Relevance
“…It is thus possible that the two different pre-reversal criteria tap into different cognitive processes rather than reflecting different ends of the same process. The TI is calculated as follows for both high and low levels of pre-reversal learning [Delillo and Visalberghi, 1994;Rumbaugh, 1997;Beran et al, 2008]: TI = reversal performance (%)/pre-reversal performance (%)…”
Section: Doesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thus possible that the two different pre-reversal criteria tap into different cognitive processes rather than reflecting different ends of the same process. The TI is calculated as follows for both high and low levels of pre-reversal learning [Delillo and Visalberghi, 1994;Rumbaugh, 1997;Beran et al, 2008]: TI = reversal performance (%)/pre-reversal performance (%)…”
Section: Doesmentioning
confidence: 99%
“…Additionally, the TI methodology has been described in great detail [Rumbaugh, 1997] so that replicability is assured and data from different labs may confidently be compared. Furthermore, reliable TI data are available for numerous primate species, including multiple capuchin individuals [Delillo and Visalberghi, 1994;Beran et al, 2008]. However, to our knowledge, none using a comparable methodology has been reported for any member of the callitrichid family to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the degree of improvement relative to baseline should be a measure of the animal's cognitive flexibility (Bitterman, 1975). Research has shown that a variety of animals, including apes and monkeys (Beran, Klein, Evans, Chan, Flemming, Harris et al, 2008;Warren, 1966), horses (Martin, Zentall, & Lawrence, 2006), rats (Bushnell & Stanton, 1991;Reid & Morris, 1992), and birds (Bond, Kamil, & Balda, 2007;Ploog & Williams, 2010), show substantial improvement with reversals, which suggests that this type of flexibility has adaptive value (Shettleworth, 1998).…”
mentioning
confidence: 99%
“…Esse arranjo experimental permite a busca por evidên-cias de learning-set de reversões e incorpora o procedimento de reversões parciais Dube, McIlvane, Callahan & Stoddard, 1993;Reis & Costa, 2002). Além disso, esse procedimento apresentou a vantagem de evitar o desenvolvimento de relações de controle não programadas, frequentemente observado em treino extensivo de reversões de discriminações simples com duas escolhas (Beran et al, 2008), e não produziu mero controle por sequências de respostas ao longo dos treinos de reversões de discriminações.…”
Section: Reversõesunclassified